Mecanismos de control nutritivo para personas con diabetes - Meza Henderson, Miryam Marlene (2022)
As we know, obesity and diabetes are a pandémic of de new century and the study of their mechanisms and nutritional management have been developing beneficially. In this paper we address their causes, consequences and ways to prevent them through physical, body and even mental health care, which includes pharmacological and non-pharmacological therapy (healthy lifestyles) through metabolic and glycemic control; these guidelines were made following the instructions of the international guidelines ALAD and ADA and others references. It is observed that there is no ideal distribution of macronutrientes and that every patient must have an individualized régimen to cover their nutritional needs and their pharmacological management, with a moderate contribution of healthy fats, moderate proteins and carbohydrates of low glycemic index, and thus be able to restore the patient’s health conditions.